Estimating the Force of Infection with Helicobacter pylori in Japan - Taishi Kayano; Ki-Deok Lee; Hiroshi Nishiura (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Although the seroprevalence against Helicobacter pylori (H. pylori) in Japan has declined over the birth year, Japanese people have yet exhibited a relatively high risk of gastric cancer. The present study employed mathematical models to estimate the time- and age-dependent force of infection with H. pylori in Japan, predicting the future seroprevalence by time and age. Methods. We investigated the published seroprevalence data against H. pylori in Japan from 1980–2018. Solving the McKendrick partial differential equation model, the seroprevalence was modeled as a function of survey year and age. Maximum likelihood estimation was conducted to estimate parameters governing the time- and age-dependent force of infection. Results. Among all fitted models, the time-dependent and age-independent model with an exponentially decaying force of infection over years was most favored. Fitted models indicated that the force of infection started to decrease during and/or shortly after the World War II. Using the parameterized model, the predicted fraction seropositive at the age of 40 years in 2018 was 0.22, but it is expected to decrease to 0.13 in 2030 and 0.05 in 2050, respectively. Conclusion. The time dependence was consistent with the decline in the force of infection as a function of the birth year. The force of infection has continuously and greatly declined over time, implying the diminished transmission of H. pylori through the time course and small chance of persistence. These findings are critical to anticipate the future decline in gastric cancer incidence.